2011
DOI: 10.7124/bc.000118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel TDRD7 isoforms

Abstract: The aim of our study was to investigate the tudor domain-containing protein 7 (TDRD7) subcellular localization, which could be linked to diverse functions of this protein within the cell. Methods. In this study we employed cell imaging technique for detecting TDRD7 subcellular localization, Western blot analysis of HEK293 cell fractions with anti-TDRD7 monoclonal antibodies and bioinformatical search of possible TDRD7 isoforms in Uniprot, Ensemble, UCSC databases. Results. We have observed specific TDRD7-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Our recent studies with employment of immunofluorescentconfocal microscopy and anti-TDRD7 (E6) monoclonal antibody indicated the presence of TDRD7 not only in the cytoplasm, but in the nucleus as well. Especially strong TDRD7 positive signal was observed in the perinuclear zone and in the region of mitotic spindle formation [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies with employment of immunofluorescentconfocal microscopy and anti-TDRD7 (E6) monoclonal antibody indicated the presence of TDRD7 not only in the cytoplasm, but in the nucleus as well. Especially strong TDRD7 positive signal was observed in the perinuclear zone and in the region of mitotic spindle formation [19].…”
mentioning
confidence: 99%
“…Our previous studies allowed us to determine TDRD7 distribution in HEK293 cells [19]. Using anti-TDRD7 monoclonal antibodies (E6) we had demonstrated that a large fraction of this protein was localized in the nucleus and perinuclear region of HEK293 cells.…”
mentioning
confidence: 99%
“…Indeed, the Tudor protein family is one of the most conserved groups of molecular determinants in germline specification (Fierro-Constaín et al 2017 ). The TUDOR domain is commonly found in a wide range of proteins that are involved in RNA metabolism and splicing, histone modification, DNA damage response, cell division, differentiation, genome stability and gametogenesis (Hosokawa et al 2007 ; Skorokhod et al 2011 ; Pek et al 2012 ). These determinants are usually organized in ribonucleoprotein complexes in the germ plasm of PGCs and/or nuage localised near nuclear pores (Fierro-Constaín et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other species, TDRD7 orthologues have been observed in cytoplasmic, mostly perinuclear positions. However, western blots of cellular fractions revealed the presence of a short isoform of human TDRD7 (60 kDa) in the nucleus, while longer isoforms were located in cytoplasmic and mitochondrial fractions (Skorokhod et al 2011 ). Moreover, Tanaka and colleagues ( 2011 ) observed the presence of TDRD7 in nuclei of mammal intermediate differentiating germ cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation